English online : a student's guide to the Internet and the World Wide Web - Crump, Eric.; Carbone, Nick. (Boston, MA : Houghton Mifflin, 1997)
Introduction to the online world. Netiquette. Preparing to enter the Internet. Electronic mail. Mailing lists: hosts for discussion groups and online communities. Telnetting on the Internet. Gopher and Lynx. File transfer protocol...
Keywords: English language; Internet; Rhetoric; Computer network resources; World Wide Web; Online data processing; Internet; English language -- Rhetoric -- Computer network resources; Academic writing -- Computer network resources; Online data processing; World Wide Web